The State’s Responses to Urban Marginality in Natalspruit - Gqoboza, Zandile Samantha (University of the Witwatersrand, Johannesburg, 2024)
This research argues that dimensions of ‘urban marginality’ are reflected in South African cities, in informal trading in poor urban peripheries; specifically, in ‘townships’ and ‘informal settlements’. One finds in post-apartheid South Africa, poor urban margins, where individuals are forced to create alternative forms of employment as a means to survive. These alternative forms of employment are part of the waiting experience of the urban poor (Auyero, 2012). The findings of this paper dispute a claim made by Yamada (1996) stating that informal self-employment is by choice and that it is economically sufficient. Contrary to the above claims the research illustrates that this form of employment is forced and is unprofitable and is therefore economically insufficient. This study therefore suggest that the post-apartheid state should formulate policies with the understanding that this sector is forced and is economically insufficient. To illustrate the above, the research focuses on the experiences of informal traders in the trading area of Natalspruit and analyze their relationship with the municipal state in Ekurhuleni.
A research report submitted in fulfillment of the requirements for the Master of Arts, In the Faculty of Humanities, Wits School of Art, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Urban marginality; informality/ informal sector; survivalist entrepreneur; SDG-11: Sustainable cities and communities